(untitled) (Abhat Journal, 2024)
All countries of the world seek to achieve stability within their societies, which requires diligent efforts to achieve peace and peaceful coexistence among their citizens. The law is an effective regulatory means in resolving disputes and conflicts between individuals and groups. Therefore, legal development must be based on diagnosing social reality and analyzing its data in order to ensure the achievement of social and legal security in parallel. In view of the state of fragmentation and instability that our Libyan society is going through today due to the spread of the culture of violence and fanaticism and the spread of chaos in all its institutions, which has made the application of traditional justice insufficient for its desired purpose. In this paper, we have tried to shed light on the concept of restorative justice, its justifications and mechanisms for applying it in our Libyan society, and to adopt the principle of reconciliation in accordance with cultural specificity and social structure in order to resolve the existing conflicts and problems radically in line with the principle of restorative and consensual settlement based on reparation of harm and compensation for victims so that the spirit of affection and tolerance prevails. Security and stability prevail. The importance of this paper lies in defining the concept of social peace, and the role of restorative justice in achieving it, in addition to the obstacles and challenges that prevent the achievement of national reconciliation. Therefore, the descriptive analytical method was used by stating and clarifying those concepts, principles, obstacles and challenges that prevent the achievement of the desired forest. A number of results have been reached that show that applying restorative justice is required at this stage and an urgent necessity in supporting and consolidating social peace.